Analisis Pengaruh Kontaminasi Sand terhadap Properties Lumpur Pemboran - Alfianto, Rycho; Ulfah, Baiq Maulinda; Rahman, Muhammad Rizqie Fathan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Sand contamination is a common issue in drilling operations, particularly in sandstone formations, as it can progressively degrade drilling fluid performance. This study aims to analyze the effect of sand contamination on drilling mud properties and the associated physical and chemical interactions affecting mud optimization. This research is an experimental laboratory study using a water-based drilling fluid system with sand contamination levels of 0%, 5%, and 10% by total mud volume. The evaluated parameters include mud weight, plastic viscosity, yield point, gel strength, pH, and filtration loss. The results indicate that sand contamination up to 5% remains within acceptable operational limits, while 10% contamination leads to significant deterioration of rheological properties, increased filtration loss, and reduced chemical stability.